Chronic kidney disease in patients with obstructive sleep apnea. A narrative review. (October 2019) - Voulgaris, Athanasios; Marrone, Oreste; Bonsignore, Maria R.; Steiropoulos, Paschalis
Summary: Prevalence of both chronic kidney disease (CKD) and obstructive sleep apnea (OSA) is continuously increasing. Moreover, the prevalence of OSA increases as kidney function declines and is higher among patients with end-stage renal disease (ESRD). In addition, OSA is recognized as a potential nontraditional risk factor for development and progression of CKD. Continuous positive airway pressure (CPAP) plays a pivotal role in the management of OSA, eliminating patients' symptoms and improving their quality of life. Recent studies suggested that CPAP treatment may have beneficial effects on kidney function among patients with OSA. This narrative review summarizes the existing knowledge on the association between CKD and OSA, with emphasis on the epidemiology, the pathophysiology of the development of CKD in OSA and vice versa, as well as the effect of CPAP on renal function.